Option Pricing under a Mean Reverting Process with Jump-Diffusion and Jump Stochastic Volatility: Nonthiya Makate, Pairote Sattayatham - Team, Support (Thai Journal of Mathematics, 2012)
An alternative option pricing model is proposed, in which the asset prices follow the jump-diffusion and exhibits mean reversion. The stochastic volatility follows the jump-diffusion with mean reversion. We find a formulation for the European-style option in terms of characteristic functions.